COVID-19, sports, and myocardial consequences - Jørstad, H. T.; Piek, J. J. (Netherlands Heart Journal, 2020)
During the first months of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, the published data led to the assumption that cardiac involvement is correlated with the severity of the clinical course of the coronavirus disease 2019 (COVID-19). Major efforts were undertaken to predict who would be at risk for severe COVID-19, successfully identifying factors such as coronary artery disease, congestive heart failure, and obstructive lung disease [1]. In many ways, these factors characterise the opposite of what constitutes the healthy and relatively young populations of (elite) athletes and highly active individuals [2]. Yet, these are the very individuals—young and with a clinical presentation of SARS-CoV-2 infection ranging from asymptomatic to mild—in whom increasingly alarming cardiac findings are being reported.